(untitled) (American Journal of Islam and Society, 2025)
There is no doubt that the topic of Islam and women has received a great deal of scholarly attention from different vantage points that serve competing interests and claims. Amidst this plethora of discourses, Asma Afsaruddin’s edited volume The Oxford Handbook of Islam and Women sheds light on the multi-faceted and diverse nature of Muslim women’s lives in the past and in the present. As Afsaruddin points out in the introduction, the volume is in conversation with some of the politicization and the idealization that the topic has encountered in both lay and academic circles, and attempts to provide a more nuanced and historicized approach that better reflects Muslim women’s lived experiences, perspectives, and manifold contributions to the Islamic tradition. It makes for a valuable reference work that helps readers navigate the minefield of political and other ideologies that revolve around Muslim women.